LITERARY LESSON OF VASYL STEFANYK IN YURII STANYNETS` CREATIVE WORKS STANYNTS - Barchan, Valentyna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The aim. The suggested literary critic research traces the influence of Vasyl Stefanyk’s creative experience upon shaping worldview, aesthetical grounds of Yurii Stanynets (1906-1994), a prose writer from Zakarpattia. On the rich literary-fictional material, the task is set to analyse the writer’s works that came out in different periods of his creative life and to reveal the “lessons of the master of psychological prose” in the planes of Yurii Stanynets’s genres and styles, as well as problems and themes. The research methods are outlined through using comparative-typological, cultural-historical and biographical methods, as a result of which the extent of Vasyl Stefanyk’s impact on Yurii Stanynets’s prose works in the periods of 20s ‒ 40s and 50s ‒ 80s of the XXth century is elucidated. The research results witness that shaping the prose mastery of the word artist from Zakarpattia was under the direct influence of the best literary models of the Ukrainian national prose writing. The writer himselfhighlights the role and significance of Vasyl Stefanyk’s novellas in that, witnessed by his “Autobiography”. Hence, the article singles out those aspects of Yurii Stanynets’s fictional practice that are brightly marked with the imprint of the creative work of the Ukrainian literature classic. In particular, the correlation of worldview and aesthetical grounds of the word artist from Zakarpattia from Vasyl Stefanyk’s worldview-aesthetical guidesis elucidated,. Simultaneously, typologically comparable parallels define the impact of the latter on Yurii Stanynets’s long and short prose, the peculiarities of his fictional thinking, that is revealed in in his external and internal structures of stories, novellas and narratives, in the peculiarity of the style manner of the prose writer from Zakarpattia. The scientific novelty lies in the fact that for the first time in contemporary Ukrainian literaryscience the comparative-typological study of creative works by Vasyl Stefanyk and Yurii Stanynetsis conducted in the field ofaspectual levels of their fictional heritage, Vasyl Stefanyk’s notable influence upon the creative work of the prose writer from Zakarpattia is proved.